Restoring Language to Literature Pedagogy: Towards an Interactive Approach - Salim, Mohammad Taher Hossain (Indonesian Journal of English Language Studies (IJELS), 2023)
English literature teaching in Bangladeshi universities has remained to be a frustrating experience for the faculties. This “frustration” is often attributed to the poor understanding of “the intellectually unequipped” and ‘linguistically unprepared’ students. This study, to understand the faculty frustration, investigates the literature teaching approaches practiced in the classes. The study also examines the role of “linguistic skill” as the learning outcome in the lesson plan of the course teachers. Finally, the paper finds that literature teaching at the tertiary level in Bangladesh does not accommodate pedagogical approaches and the linguistic skill of the students is not given the required priority in the teaching process. This paper, therefore, recommends an Interactive Approach in which language is to be integrated as one of the learning outcomes.